Becoming a Place - Yerlesmek : proje4L. - Elgiz, Can; Istanbul Musemu of Contemporary Art, Istanbul (Istanbul : Proje4L - Istanbul Museum of Contemporary Art, 2001)
Alptekin, Huyesin ; Altay, Can ; Altindere, Halil ; Carlsson, Tina ; Ersen, Esra ; Gongrich, Erik ; Gursoytrak, Hakan ; Karamustafa, Gulsun ; Murtezaoglu, Aydan ; Sangar, Bulent ; et al.
Becoming a Place, Istanbul Museum of Contemporary Art, Istanbul , September 21 - November 24, 2001
kunstcatalogus